Climate smart agriculture in South Asia: Technologies, policies and institutions - Pal, Barun Deb; Kishore, Avinash; Joshi, Pramod Kumar; Tyagi, Narendra K. (Springer, 2019)
This book discusses various climate smart agro-technologies, their technical and economic feasibility across heterogeneous agro-climatic conditions, assessing farmers’ willingness to adopt those technologies, impact of climate smart technology in agricultural production and possible policy and investment opportunities to upscale it. Containing eight chapters, the book starts with a discussion about the methodological aspects of priority setting of the farm technologies across various regions of South Asia including Eastern Indo-Gangetic plain, Western Indo-Gangetic Plain and arid regions. Using data from field based trials and expert solicitations, the book next deliberates on a list of feasible technologies, assessed by constructing climate smart Feasibility Index.